Surface modification of biochar composite made from tea waste for the removal of selected organic pollutants from aqueous medium - Mashoene, Tumelo Nortica (Vaal University of Technology, 2022)
Domestic, agricultural, and industrial waste has been investigated as a substitute for activated carbon adsorbents. This research converted waste tea-based adsorbent, coupled with reduced graphene oxide, and further modified with deep eutectic solvents. This innovative biochar modification was investigated to overcome the limitations of the tea-waste biochar nanocomposite alone and the removal of organic contaminants from simulated wastewater. Fourier Transformed Infrared Spectroscopy (FTIR), X-ray diffraction (XRD), Scanning Electron Microscopy-Energy Dispersive X-Ray Spectroscopy (SEM–EDS), Brunauer, Emmett, and Teller (BET) surface area analysis, and pH at point of zero charge (pH PZC) was used to characterize the synthesized materials (biochar, biochar/reduced graphene oxide (biochar/rGO), biochar/reduced graphene oxide/deep eutectic solvent-cetyltrimethylammonium bromide (biochar/rGO/DES-CTAB), and biochar/reduced graphene oxide/deep eutectic solvent-glycerol (biochar/rGO/DES-glycerol)). The results showed that the principal material biochar was modified by a show of added functional groups and surface structural changes. The materials biochar, biochar/rGO, biochar/rGO/DES-CTAB, and biochar/rGO/DES-glycerol were applied for the removal of ZDV and phenol from the aqueous medium. Batch adsorption studies were conducted to optimize operating parameters such as adsorbent dose, solution pH, contact time, and initial concentration. Pseudo-first-order (PFO), Pseudo-second-order (PSO), and intraparticle diffusion (IPD) kinetic models were determined to investigate the mechanism of the adsorption process. The coefficient of correlation, R2, was used to determine the best fit of the kinetic models. The adsorption results showed that DES-glycerol-modified adsorbent was more efficient in removing the pollutants ZDV and phenol than biochar, biochar/rGO, and biochar/rGO/DES-CTAB adsorbents. In addition, the results showed that an acidic medium of pH 2.00 and a contact time of 1h30min and 30 min is sufficient for removing ZDV and phenol respectively, from an aqueous medium. The experimental data best fit into PSO models and assumed a variety of interactions between the adsorbent surface and adsorbate molecules and IPD wasn’t the only rate-determining step. The Langmuir and Freundlich models further examined the experimental data to assess the adsorbate-adsorbent interactions at equilibrium. Equilibrium experiments revealed that adsorption adhered to the Langmuir isotherm, demonstrating the homogeneity of adsorption sites. This study demonstrates the feasibility of the conversion and modification of common tea waste into a useful adsorbent for the remediation of organic contaminants from wastewater, thus creating an opening for the application of waste tea-based adsorbent in industrial settings.
M. Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Domestic, agricultural and industrial waste; Waste tea-based absorbent; Tea-waste biochar nanocomposite; Removal of organic contaminants from wastewater; Conversion and modification of common tea waste; Remediation of organic contaminants; Biochar; Dissertations, Academic -- South Africa.; Organic water pollutants.; Biochar.; Nanostructured materials.; Composite materials.